Univerzalni programator za programiranje bipolarnih PROM-ov in PLA-jev - Štravs, F. (Informatica (Ljubljana), 1980)
The programming of bipolar circuits is a relatively pretentious task since the required pulses have to be shaped differently in accordance with technology differencies of the manufacturers and can not be unified. The programmer must be able to generate pulses in accordance with requirements. The article describes an universal and modulary built programming board for pulse generation. For different circuits the programming modules of the 6800 family microcomputer have to be known. As an example the programming of 74 S 288 PROM, which performs the function of IDM 29811 Next-Address Controler, is described.
Keywords: bipolarna vezja; programiranje; univerzalni programator